Non-alcoholic beverage and fast-food consumption, among first- and fourth-year nursing students in Madrid - Ortuño-Soriano, Ismael; Zaragoza-García, Ignacio; Becerro-de-Bengoa-Vallejo, Ricardo; Losa-Iglesias, Marta Elena; López-Herranz, Marta; Posada-Moreno, Paloma (Archivos Latinoamericanos de Nutrición (ALAN), 2022)
Sugar-sweetened beverages and fast-food consumption have been associated with non-communicable diseases. Objective. Was to analyze consumption of non-alcoholic beverage and fast-food consumption among first- and fourth-year nursing students. Materials and methods. A questionnaire-based survey was conducted among first-and fourth-year nursing students in Madrid, Spain. Anthropometric data (weight and height) and demographic data were collected, as were data on consumption of specific foods and beverages. Results. The survey was completed by 436 students. Mean (SD) age was 22.0 (6.8) years, 84.1 % of were women.26.2 % of the students were underweight; 6.3 % were overweight. Consumption of sugar-sweetened beverages and diet drinks was moderate. Slightly more than three-quarters of the students (75.5 %) purchased fast food in the previous month. Burger bars were the most frequently visited fast-food outlet (77.2 %). A direct relationship was observed between BMI and fast-food consumption (rho = 0.099; p = 0.042) and between BMI and consumption of diet cola or carbonated drinks (rho = 0.120; p = 0.013). Conclusion. We provide new epidemiological data from a specific university population that could be useful to promote more studies that help design appropriate strategies to increase a healthy lifestyle. Las bebidas azucaradas y el consumo de comida rápida se han asociado con enfermedades no transmisibles. Objetivo. Analizar el consumo de bebidas no alcohólicas y el consumo de comida rápida entre estudiantes universitarios de primer y cuarto curso de enfermería. Materiales y métodos. Cuestionario validado entre estudiantes de enfermería de primer y cuarto año en Madrid, España. Se recopilaron datos antropométricos (peso y altura) y demográficos, así como datos sobre consumo de alimentos y bebidas específicos. Resultados. La encuesta fue completada por 436 estudiantes. La edad media (DE) fue de 22,0 (6,8) años, el 84,1 % eran mujeres; el 26,2 % de los estudiantes tenían bajo peso y el 6,3% mostraban sobrepeso. El consumo de bebidas azucaradas y bebidas dietéticas fue moderado. Más de tres cuartas partes de estudiantes (75,5%) compraron comida rápida en el mes anterior. Las hamburgueserías fueron el restaurante de comida rápida más visitado (77,2%). Se observó una relación directa entre el IMC y el consumo de comida rápida (rho = 0,099; p = 0,042) y entre el IMC y el consumo de refrescos dietéticos o bebidas gaseosas (rho = 0,120; p = 0,013). Conclusión. Aportamos nuevos datos epidemiológicos de una población universitaria concreta, que podrían ser de utilidad para promover más estudios que ayuden a diseñar estrategias adecuadas para incrementar un estilo de vida saludable.